The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1096/fj.201901536rr
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence repeats identify numerous Type I restriction‐modification systems that are potential epigenetic regulators controlling phase‐variable regulons; phasevarions

Abstract: Over recent years several examples of randomly switching methyltransferases, associated with Type III restriction-modification (R-M) systems, have been described in pathogenic bacteria. In every case examined, changes in simple DNA sequence repeats result in variable methyltransferase expression and result in global changes in gene expression, and differentiation of the bacterial cell into distinct phenotypes.These epigenetic regulatory systems are called phasevarions, phase-variable regulons, and are widespre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 83 publications
(306 reference statements)
2
30
0
Order By: Relevance
“…Our systematic analysis of REBASE identified Type I loci containing multiple hsdS genes where we detect IRs in a range of commensal organisms, such as Bacteroides fragilis and multiple Ruminococcus species, in environmental bacterial species such as Leuconostoc mesenteroides and in a number of Lactobacillus species that are important to the biotechnology and food production industries (Data Set S3). This reflects our previous studies where we observed simple sequence repeats that mediate phase variation in multiple Type I (14) and Type III methyltransferase genes (13) present in a variety of commensal and environmental organisms.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our systematic analysis of REBASE identified Type I loci containing multiple hsdS genes where we detect IRs in a range of commensal organisms, such as Bacteroides fragilis and multiple Ruminococcus species, in environmental bacterial species such as Leuconostoc mesenteroides and in a number of Lactobacillus species that are important to the biotechnology and food production industries (Data Set S3). This reflects our previous studies where we observed simple sequence repeats that mediate phase variation in multiple Type I (14) and Type III methyltransferase genes (13) present in a variety of commensal and environmental organisms.…”
Section: Discussionsupporting
confidence: 89%
“…A broad range of bacterial species encode these systems. Our previous work showed that 2% of Type I hsdM and 7.9% of Type I hsdS genes contain SSRs (14). Together with our findings in this study, this means that 13.8% of all Type I systems are capable of phase-variable expression.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations